2022
DOI: 10.1111/ceo.14113
|View full text |Cite
|
Sign up to set email alerts
|

Infectious keratitis: A review

Abstract: Globally, infectious keratitis is the fifth leading cause of blindness. The main predisposing factors include contact lens wear, ocular injury and ocular surface disease. Staphylococcus species, Pseudomonas aeruginosa, Fusarium species, Candida species and Acanthamoeba species are the most common causal organisms. Culture of corneal scrapes is the preferred initial test to identify the culprit organism. Polymerase chain reaction (PCR) tests and in vivo confocal microscopy can complement the diagnosis. Empiric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 130 publications
1
112
0
3
Order By: Relevance
“…Case 1 is a typical case of a CL wearer infective AK that is generally associated with inappropriate lens maintenance and exposure to tap or contaminated water sources [ 17 ]. AK is a sight-threatening condition that can lead to blindness with slow progression and can be often misdiagnosed as herpes simplex virus (HSV) or other corneal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Case 1 is a typical case of a CL wearer infective AK that is generally associated with inappropriate lens maintenance and exposure to tap or contaminated water sources [ 17 ]. AK is a sight-threatening condition that can lead to blindness with slow progression and can be often misdiagnosed as herpes simplex virus (HSV) or other corneal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular predisposing factors, such as contact lens wear, previous topical steroid use, ocular surface disease, and trauma, are main risks for infectious keratitis. 8,10 In the previous report, all cases received ceftazidime eyedrops combined with systemic antibiotics such as intravenous ceftazidime or oral amoxycillin-clavulanic acid. Subconjunctival ceftazidime injections were prescribed on alternate days to treat two cases with subconjunctival abcesses.…”
Section: Discussionmentioning
confidence: 99%
“…In infectious keratitis, corneal ulcers will occur after invasion of viruses, bacteria, and other pathogenic factors into the cornea ( Cabrera-Aguas et al, 2022 ). Faik et al reported that archipelago keratitis led to a significant increase in COD ( Orucoglu et al, 2014 ).…”
Section: Factors Influencing Cod In Healthy People and Patients With ...mentioning
confidence: 99%